Targeted Oral Fixed-Dose Combination of Amphotericin B-Miltefosine for Visceral Leishmaniasis - Fernández-García, Raquel; Walsh, David; O’Connell, Peter; Passero, Luiz Felipe D. [UNESP]; de Jesus, Jéssica A. [UNESP]; Laurenti, Marcia Dalastra; Dea-Ayuela, María Auxiliadora; Ballesteros, M. Paloma; Lalatsa, Aikaterini; Bolás-Fernández, Francisco; Healy, Anne Marie; Serrano, Dolores R. (American Chemical Society (ACS), 2025)
The incidence of visceral leishmaniasis (VL) remains a significant health threat in endemic countries. Fixed-dose combination (FDC) of amphotericin B (AmB) and miltefosine (MLT) is a promising strategy for treating VL, but the parenteral administration of AmB leads to severe side effects, limiting its use in clinical practice. Here, we developed novel FDC granules combining AmB in the core with a MLT coating using wet granulation followed by the fluidized bed technology. The granules maintained the crystalline structure of AmB throughout manufacturing, achieving an AmB loading of ∼20%. The MLT coating layer effectively sustained AmB release from 3 to 24 h following Korsmeyer-Peppas kinetics. The formulation demonstrated remarkable stability, maintaining >90% drug content for over a year at both 4 °C and room temperature under desiccated conditions. In vivo efficacy studies in Leishmania infantum-infected hamsters showed 65-80% reduction in parasite burden in spleen and liver, respectively, suggesting potential as an oral alternative to current VL treatments. Uncoated and coated granules demonstrated comparable performance in key aspects, including in vivo efficacy and long-term stability.
Keywords: amphotericin B; coating; fixed-dose combination; miltefosine; oral delivery; visceral leishmaniasis